Do People Vote with Their Feet? An Empirical Test of Tiebout's Mechanism - Banzhaf, H. Spencer; Walsh, Randall P (American Economic Review, 2008)
Charles Tiebout's suggestion that people “vote with their feet” for communities with optimal bundles of taxes and public goods has played a central role in local public finance for over 50 years. Using a locational equilibrium model, we derive formal tests of his premise. The model predicts increased population density in neighborhoods experiencing exogenous improvements in public goods and, for large improvements, increased relative mean incomes. We test these hypotheses in the context of changing air quality. Our results provide strong empirical support for the notion that households “vote with their feet” for environmental quality. (JEL H41, H73, Q53, R23)